PABRA markets evolution and precedents - Birachi, Eliud Abucheli; Mutua, Mercy; Rubyogo, Jean-Claude (2022)
PABRA’s market facing approach has evolved over the last 2 decades, with a strong client focus. It has evolved from participatory planting breeding through participatory variety selection, niche market breeding, value chain focus, innovation platforms, demand led breeding and to corridor approach and lately with digital inclusion. The current demand led corridor model was introduced by PABRA to provide a framework for catalyzing and intensifying production, distribution and marketing and consumption of beans and bean products.